Symposium 3: Open, networked and connected learning: Bridging the formal/informal learning divide in higher education - Cronin, Catherine (Proceedings of the International Conference on Networked Learning, 2016)
In the age of ‘networked individualism’ (Castells, 2004; Rainie & Wellman, 2012) students enter higher education as networked individuals with extant and diverse informal learning practices, networks and identities. While higher education institutions typically focus on Virtual Learning Environments (VLEs) as the primary online hubs for students, students themselves use a wide range of online tools and resources for communicating, coordinating, collaborating and learning, i.e. building their own Personal Learning Environments (PLEs). While institutions and academic staff tend to see institutional VLEs and learner-chosen PLEs as separate entities, learners do not (Reed, 2013). Students often find that their informal learning practices sit uneasily within the formal education environments within which they study. Open education, particularly open educational practices (OEP), is one way that the formal/informal learning divide in higher education may be bridged. Advocates of open education highlight its potential to make education more inclusive and equitable. However, some critiques of open education view such claims as utopian, ignoring the workings of systemic power and privilege. This paper explores the formal/informal learning divide in higher education, the complexities and different interpretations of open education, and potential benefits for students and educators in bridging the formal/informal learning divide, i.e. working together within higher education learning communities but also as nodes in “broad networks of distributed creativity” (J. Ito, 2011).